Firm Reputation and Incentives to Milk Pending Patents - Johannes Koenen; Martin Peitz (Center for Economic Studies and ifo Institute (CESifo), 2013)
In this paper we develop a theory of patenting in which a firm preserves its reputation to only apply for a patent whenever a truly patentable idea has been generated. Firms have a short-run incentive to deviate and receive additional rents from unworthy pending patents, as well as potential rents from PTO mistakes in granting patents. We provide conditions for reputation to be preserved in equilibrium and analyze which market environments are favorable for such an equilibrium to exist. In particular, we analyze the merits of different patent systems.
Keywords: L15; L22; O34; 330; pending patents; reputation; patent quality; patent office policy